印 尼 华 人 的 宗 教 信 仰 - Andyni Khosasih (Bina Nusantara University, 2007)
The population of Chinese descendants in Indonesia reaches 7 millions. Their success cannot be taken separated from the culture embedded. On the other hand, understanding Chinese cultures cannot be separated from analyzing Chinese believes. There is a long history of Chinese religion. It has also portrayed the differences of cultures from which the portrayal forms unique symbol and characterization of its people. The outstanding quality of religions of Chinese-Indonesians is the adaptability, acceptance and openness. Indonesian Government, which has the policy of uniformity after the 1960 causes the breach of Chinese heritage for a long period of time. This has cost socio-structural gaps and multicultural disparity which is getting wider between east and west cultures. This thesis discusses the history and developments of Chinese-Indonesian religions with future predictions uphold.